Pengaruh Beban Kerja terhadap Kinerja Karyawan PT Mitra Rajawali Banjaran - Meilany, Lisda; Ilma, Robbi Zidni (Economic Reviews Journal, 2024)
This research ains to determine the effect of workload on employee performance at PT Mitra Rajawali Banjaran. This research is categorized as descriptive research and a cuantitative approach with an instrument in the form of a questionnaire the population in this study was 66 employees. Sampling was taken using simple random sampling. Data collection uses questionnaires and observation. Test the validaty of the instrument using pearson product moment while testing realibility using Cronbanch Alpha with the help of SPSS. The measuring tool is proven to be valid and reliable for research instruments this research hypothesis test uses simple linear regression analysis, Determination (R2), t test (Partial). The research result are proven workload has a significant positive effect on employee.